Discrete-event system simulation - Banks, Jerry; Carson, John S.; Nelson, Barry L.; Nicol, David M. (Pearson Education, 2014)
This text provides a basic treatment of discrete-event simulation, including the proper collection and analysis of data, the use of analytic techniques, verification and validation of models, and designing simulation experiments.